Analysis of fault bend folding kinematic models and comparison with an analog experiment. (May 2021) - Plotek, Berenice; Guzmán, Cecilia; Cristallini, Ernesto; Yagupsky, Daniel
Abstract: Analog modeling of a flat-ramp-flat fault system was performed and its geometry and displacement field were compared to those of different kinematic models such as classical fault bend folding, fault parallel flow, incline-shear, curvilinear hinge, and backlimb trishear. To obtain the displacement vectors of the analog experiment, a Particle Image Velocimetry was performed. All analyzed kinematic models could explain the general configuration of the fault bend folding. However, only backlimb trishear could represent the geometry, directions of particle displacements, and relations between the displacements' vectors. We propose in this paper that the combination of different asymmetry angles and different apical angles of the backlimb trishear model for each bend in a fault bend fold could be a very versatile and general kinematic model for simulating fault bend folds. Backlimb trishear apical angle can be used to control the shape of the hinges of a fold, while the asymmetry can be used to convolve the velocity of the particles above the fault. Both apical angle and asymmetries different from zero imply thickness changes. Fault bend folds with high inclination forelimbs can be reproduced with high positive asymmetries in the anticline bends of the fault. Highlights: Analog model was performed to obtain the velocity field during deformation. Documentation of velocity vectors comes from particle image velocimetry. Backlimb trishear can represent the geometry and directions of particles velocities. Steeper-dipping forelimbs can be reproduced using high positive asymmetries. Backlimb trishear apical angle can be used to control the shape of the hinges.